Improved mechanical properties of bitumen modified with acetylated cellulose fibers. (1st May 2018) - Desseaux, Solenne; dos Santos, Salomé; Geiger, Thomas; Tingaut, Philippe; Zimmermann, Tanja; Partl, Manfred N.; Poulikakos, Lily D.
Abstract: Temperature sensitivity of bitumen modified with acetylated microfibrillated cellulose (MFCac), both in the low and high temperature ranges, is significantly decreased. The complex shear modulus for an MFCac content of 2 wt% was 10 times higher than for bitumen alone. In addition the phase angle at high temperatures indicates increased elastic behavior that results in favorable properties with respect to rutting. On the low temperature side (−25 °C), the deformation to failure in fracture toughness tests was around 100 times higher with MFCac modified bitumen than for the non-modified one whereas the failure forces were similar. Graphical abstract: Image 1